Pengembangan Kapasitas dan Kelembagaan Kelompok Pemberdayaan Ekonomi Berbasis Kewilayahan (PEW) - Bening Hadilinatih; Susi Widjajani (Universitas Proklamasi 45 Yogyakarta, 2016)
Hidayah PEW group and Khasanah PEW group, in Village Pringgokusuman, District of Yogyakarta Gedong Tengen, a group of beneficiaries of Area Based Economic Empowerment Program in the city of Yogyakarta. Currently these two groups on the problem: 1). The weakness of the organizational aspects of the institutional group, yet have the institutional rules are clear, 2) Still Weak aspects of group administration, system administration and financial management is still very simple, 3) Low skills of administrators in the management of savings and loans, the ability of the management of the organization low group 4). The low activity is productive business (entrepreneurship) members. To help overcome the problems in both groups of partners, it will do service activities using the approach of counseling, training and mentoring. The training consists of training the administrative and accounting groups, institutional management and Cooperative Training, Computer Training & Practice (Ms.Word & Ms Excel), entrepreneurship training and counseling regarding the procedure for the preparation of Statutes and Bylaws. Participants of the training consisted of officials from each of the partners. The objectives and targets to be achieved from each activity are as follows: 1) Extension of the procedure for preparing the Statutes and Bylaws; to improve the knowledge and ability to prepare a document for Statutes and Bylaws group. 2). Training Administration and accounting group; to improve the knowledge and skills of participants in financial administration and bookkeeping savings group savings and loan accounting. 3). institutional and cooperative management training; that the board had knowledge of the institutional and cooperative management. 4) computer training; to improve the knowledge and skills to use computers as supporting the administration of the savings group. 5) entrepreneurship training; to improve understanding of entrepreneurship and increased interest, the spirit of entrepreneurship, and increasing entrepreneurial activity of the participants. Target to be gained from the mentoring activities are: 1) orderly administration PEW Group includes the administrative requirements of the organization and financial adminstration 2) . morale and motivation entrepreneurship 3). Improving the skills of the board to operate a computer for administrative support group. 4). Establishment of complete annual financial statements (statements Balance Sheet, of net income, Cash Flow Statements) 5). Job description Establishment Board.